A tissue-based simulation model for cardiopulmonary bypass cannulation/decannulation training. (October 2020) - Luo, Xiaokang; Luo, Fuliang; Li, Bo; Li, Bin; Tang, Yue; Sun, Hansong
Background: Cardiopulmonary bypass is the basis of open heart surgery. Through simulation-based learning, residents may receive structured training of cardiopulmonary bypass techniques. Therefore, we built a high-fidelity, tissue-based simulation model for cardiopulmonary bypass cannulation/decannulation training. Methods: The core of the model is a whole block of cadaveric animal heart and lung. The discarded membrane oxygenators are used as blood reservoirs. The tubing and suckers recycled from animal experiments are washed and reused. To set up the model, the cadaveric heart and lung are placed into a container of appropriate size. The "arterial" tubing is connected with a pressure gauge, the distal aorta, the superior vena cava, and arterial cannula, respectively. The "venous" tubing is composed of three independent catheters, respectively, for the practice of venous cannulation, for the connection of sucker and for the practice of placing left atrial/ventricular vent. All tubes are installed on the roller pumps to maintain the correct flow direction. A technician should be responsible for operating the heart–lung machine, clamping and releasing the specific segments of tubing, adjusting the pressure, and cooperating with the trainees to practice. Results: Using the simulation model, 18 residents underwent cardiopulmonary bypass techniques training, with an average satisfaction of 8.94 points. The mean score on the overall fidelity of the simulation model assessed by nine experienced cardiothoracic surgeons was 8.67 points. Conclusion: The tissue-based simulation model has a certain degree of realism. Cardiac surgery residents can practice necessary cardiopulmonary bypass cannulation/decannulation techniques by this model.